Rancang Bangun Aplikasi Inventory M&G Konveksi Berbasis Web Terintegrasi n8n dengan Framework Laravel - Aulidya, Mishel; Jaman, Jajam Haerul; Yusup, Dadang (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
The development of digital technology encourages MSMEs to implement more structured data management systems, especially in businesses with complex production and distribution processes. M&G Konveksi, a clothing manufacturing service (CMT), still records material distribution and production results using physical documents, causing distribution tracking, data verification, and production monitoring processes to be carried out manually. This study aims to design and develop a web-based inventory application integrated with workflow automation to support material recording, distribution, production reporting, and operational monitoring at M&G Konveksi. The system was developed using Laravel and ReactJS and integrated with the n8n platform to support overdue notifications and automatic operational recaps. The development method used in this research is the Prototype model, while system testing was conducted using Black Box Testing and User Acceptance Testing (UAT). The results show that all system features function properly and achieve user acceptance rates above 96%. The system is able to support centralized recording and distribution monitoring while helping operational information to be presented in a more structured manner.